Exploring motivations, information behavior, perceptions, and intentions among dietary supplement users: a cross-sectional survey study in Germany - Janzik, Robin; Geppert, Johanna; Müller, Patricia; Notz, Inka; Obstfeld, Henri; Roth, Bianca; Volpers, Anna-Maria; Böl, Gaby-Fleur (Frontiers in Nutrition, 2025)
ObjectiveThe use of vitamins, minerals, or botanicals via dietary supplements (DS) is increasing in the general population despite unclear benefits and the potential risks they pose to otherwise healthy individuals. A number of studies have made attempts to explain past use based on isolated individual (e.g., age), motivational (e.g., maintenance of health), informational (e.g., labeling), or perceptual (e.g., risks and benefits) variables. However, little research has examined explaining factors comprehensively among users, or explored future intentions to expand use beyond one’s current consumption.MethodsThis study aimed to address these gaps by analyzing nationally representative survey data from Germany (N = 1,071). Participants were quota-sampled based on gender and age groups, educational levels, and federal states. Identifying DS users was based on the self-reported intake of 61 different substances, while measurements included items on health-related characteristics as well as DS-related motivations, information behavior, perceptions, attitudes, and intentions.ResultsConsistent with prior research, DS users (76.9%, n = 824) tended to be female, younger, more health-conscious, and health-literate compared to non-users. Analysis of user data suggested five distinct motivational factors: preventive, social, vulnerable, unhealthful, and situational. Users reported to receive information about DS from different sources only rarely and to feel only moderately informed. Further, users’ perceived risk and benefit of using DS were inversely related and associated with their general attitude toward the substances. Intentions to expand use were predicted by younger age, preventive as well as social motivations, and benefit perceptions.ConclusionThese results indicate that both past and future DS use is associated with diverse reasoning and own, primarily positive, judgements, potentially rooted in a confounding of perceived risk and benefit. Science communicators may build on these results by considering the conditions in which decisions for DS use are made.